3D Printing for Bone-Cartilage Interface Regeneration - Xu, Jialian; Ji, Jindou; Jiao, Juyang; Zheng, Liangjun; Hong, Qimin; Tang, Haozheng; Zhang, Shutao; Qu, Xinhua; Yue, Bing (Frontiers in Bioengineering and Biotechnology, 2022)
Due to the vasculature defects and/or the avascular nature of cartilage, as well as the complex gradients for bone-cartilage interface regeneration and the layered zonal architecture, self-repair of cartilage and subchondral bone is challenging. Currently, the primary osteochondral defect treatment strategies, including artificial joint replacement and autologous and allogeneic bone graft, are limited by their ability to simply repair, rather than induce regeneration of tissues. Meanwhile, over the past two decades, three-dimension (3D) printing technology has achieved admirable advancements in bone and cartilage reconstruction, providing a new strategy for restoring joint function. The advantages of 3D printing hybrid materials include rapid and accurate molding, as well as personalized therapy. However, certain challenges also exist. For instance, 3D printing technology for osteochondral reconstruction must simulate the histological structure of cartilage and subchondral bone, thus, it is necessary to determine the optimal bioink concentrations to maintain mechanical strength and cell viability, while also identifying biomaterials with dual bioactivities capable of simultaneously regenerating cartilage. The study showed that the regeneration of bone-cartilage interface is crucial for the repair of osteochondral defect. In this review, we focus on the significant progress and application of 3D printing technology for bone-cartilage interface regeneration, while also expounding the potential prospects for 3D printing technology and highlighting some of the most significant challenges currently facing this field.